The colony number of Streptococcus mutans and Lactobacillus in saliva of dental caries and free caries children - Seno Pradopo (Dental Journal (Majalah Kedokteran Gigi), 2008)
Streptococcus mutans (S. mutans) are regarded as the main initiator microorganism of caries, with Lactobacilli participating on caries progression, due to its carcinogenic capacity. The purpose of this study was to examine the number of S. mutans and Lactobacillus sp in children with in children’s saliva with dental caries and free caries. Twenty children attending the Paediatric Dental Clinic in Airlangga University participated in our study. Their age ranged from 1–14 years old. Subject was divided into two groups, which were study group consisting of 10 children with 3–5 dmft/DMFT and control group with 10 caries free children. Subjects were examined and their caries number was recorded using WHO index. Stimulated saliva was collected from each subject for bacterial assessment. Colony counting of S. mutans and Lactobacillus sp count in each saliva sample group were done. The study showed that subject with 3–5 dmft/DMFT had higher number of S. mutans and Lactobacillus sp than caries free.